THE ROLE OF FATHER IN PROBLEMATICAL FAMILIES: QUALITATIVE ANALYSIS - Kaučikienė, Jurga; Švedaitė-Sakalauskė, Birutė (Socialinė teorija, empirija, politika ir praktika, 2007)
The research "Father’s role in problematical families" was arranged in order to understand how fathers perceive their role, what are expectations, performing problems, happiness, what are social, economical and political factors. There was performed qualitative research in this work. The research goal was: to describe and analyse father’s role and its development features in problematic, poor families. According to the results, there’s strong patriarchal approach in problematical families: all the members expect father to represent their family in society and earn enough money. Mother takes care at home. Fathers usually don’t full fill this role because of alcohol abuse and low communication and job skills, so there’s less space at home is left for them. Women sometimes manipulate their good positions at home and better relationships with children: if man doesn’t earn enough money for family, if he behaves too bad, he can be eliminated from family for some time. But he comes back because of families economical dependence and he continues to use alcohol and violence. Social policy also doesn’t produce better conditions for the fathers of problematical families to fulfill their roles, not to feel humiliated because of their functions failure. So only the single mothers are seen in social security field.